ISOLATION AND IDENTIFICATION OF TRICHOPHYTON VERRUCOSUM IN CATTLE OF DIYALA GOVERNMENT - Azhaar H. Handi1 , Ahmed Hanash Al-Zuhairi2; Anas A. Humadi (Chelonian Research Foundation, 2023)
Skin fungi are widespread in cows and cause health problems for humans and pose an economic and public health risk. The aim of this study is to isolate and diagnose the fungal causes that cause ringworm in cows. They were studied using direct screening methods, culturing the samples on SDA and characterizing them, and PCR technology. One hundred samples were collected from cows (male and female, with age ranged between less than year to four years) in Diyala Governorate. The study was from the October of 2022 to the July of 2023, and the results showed 14% infected cow by different dermatophytes causes included a high percentage of the causative factor for infection with the fungus T. verrucosum percentage7(50%) .The result was Dermatophytes accession species number( OR362821.1). Keywords : dermatophytosis, T. verrucosum , Genetic tree , ringworm infection, cattle